KOMPETENSI KEPEMIMPINAN PROJECT MANAGER PADA PROYEK PENGEMBANGAN APLIKASI BANK INDONESIA - Rifanda Yulio Difelani; Hardiansyah, Hardiansyah (Juremi: Jurnal Riset Ekonomi, 2025)
This study aims to identify and analyze the leadership competencies required by a Project Manager (PM). The research employs a qualitative approach using a case study method. Data were collected through in-depth interviews with Project Managers, System Analysts, and project team members, and were analyzed using NVivo 12 software to generate thematic coding, including open coding, axial coding, and selective coding. The results show that the key competencies a PM must possess include cross-unit communication skills, flexible leadership, decisiveness in decision-making, conflict and stress management, and the ability to build trust among team members and stakeholders. Furthermore, soft skills training and project management certification have proven to support leadership effectiveness in guiding teams toward achieving project goals. This research reinforces the importance of a holistic leadership approach that integrates technical, interpersonal, and emotional aspects in the execution of strategic projects within the national banking sector.